Gender Wage Gap: Evidence from Employment in Informal Sector - Fakhriza Akbar (Pusbindiklatren Bappenas, 2022)
The gender wage gap is still a common phenomenon in many developing countries, especially in the informal sector. As opposed to the formal sector, the gender wage gap seems more adverse in the informal sector, where women are often in unfavourable situations to lessen the substantial wage gap between them and men. This study examined the gender earnings gap from the lower level to the upper level of the wage distribution in informal sector employment using the Indonesian National Labor Survey in 2019. While the Oaxaca-Blinder method only looked at the wage gap from the differences in mean values, this research used the Recentered Influence Function (RIF) to reveal the gaps in the wage distribution. The research found the presence of a weak sticky floor effect across the wage distribution. The gender earnings gap decreased as we moved from the lower wage distribution to the upper wage distribution. Furthermore, the structure effect or unexplained factors contributed to the most prominent share of the gap that forms the wage difference for the entirety of the wage distribution, ranging from 70 per cent. Having examined the individual characteristics, education was found to be the most prominent factor that can help narrow the gap.